2015
DOI: 10.1016/j.vaccine.2015.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant H7 hemagglutinin forms subviral particles that protect mice and ferrets from challenge with H7N9 influenza virus

Abstract: A novel avian-origin influenza A H7N9 virus emerged in China in 2013 and continues to cause sporadic human infections with mortality rates approaching 35%. Currently there are no approved human vaccines for H7N9 virus. Recombinant approaches including hemagglutinin (HA) and virus-like particles (VLPs) have resulted in experimental vaccines with advantageous safety and manufacturing characteristics. While high immunogenicity of VLP vaccines has been attributed to the native conformation of HA arranged in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 51 publications
1
31
1
Order By: Relevance
“…However, mice immunized with two doses of the unadjuvanted baculovirus VLP vaccine still lost 10−15% of their initial body weight after challenge with 3.6 LD50 A/Anhui/1/2013. More recently, weight lost and partial (80%) protection after challenge with 10 LD50 A/Anhui/1/2013 was observed in mice vaccinated IN with two doses of 5 g of unadjuvanted recombinant baculovirus-origin H7 subviral particles 3 weeks apart [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, mice immunized with two doses of the unadjuvanted baculovirus VLP vaccine still lost 10−15% of their initial body weight after challenge with 3.6 LD50 A/Anhui/1/2013. More recently, weight lost and partial (80%) protection after challenge with 10 LD50 A/Anhui/1/2013 was observed in mice vaccinated IN with two doses of 5 g of unadjuvanted recombinant baculovirus-origin H7 subviral particles 3 weeks apart [25].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, retrovirus gag was used in place of M1 [15]. The HA antigen is the major vaccine component, which induces neutralizing antibodies preventing infectious virus from entering cells [4, 16, 17]. Expression within VLPs increases immunogenicity of the HA antigen [12, 18].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that purified rH3 HA forms rosette-shaped subviral particles (SVPs) of approximately 30–50 nm in diameter [66]. We recently prepared the full-length H7 rHA from A/Anhui/1/2013 (H7N9) using a modified purification conditions for rH7 HA [67]. Similarly to a previous study [40], we found that purified rHA is arranged into particulate structures, or subviral particles (SVP), with approximately 20 nm in diameter (Figure 4).…”
Section: Subunit Rha Vaccinesmentioning
confidence: 99%
“…Thus, it is likely that formation of SVP mimics to some extent the conformational epitopes of the virus, which can explain the high immunogenicity of influenza rH7 HA. Recent data demonstrated that SVPs comprised of the full-length rHA from A/Anhui/1/2013 (H7N9) are immunogenic and protective in animal models [67]. …”
Section: Subunit Rha Vaccinesmentioning
confidence: 99%